Biological nascent evolution of snail bone and collagen revealed by nonlinear optical microscopy. Issue 8 (30th May 2019) - Li, Rui; Wang, Lei; Mu, Xijiao; Chen, Maodu; Sun, Mengtao
Abstract: Using nonlinear optical microscopy of coherent antistokes Raman scattering (CARS), second harmonic generation (SHG) and two‐photo excitation fluorescence, we in situ observed how the collagen and the bone grow synergistically and competitively during nascent biological evolution. The sds CO 3 2 − and PO 3 2 − ions were first observed to be dispersed in the liquid environment, and the collagen was observed 2 days later. With the help of the collagen, the CO 3 2 − and PO 3 2 − ions gradually moved closer to the collagen, and then the bone was produced in the forms of CaCO3 and CaPO3 . When the bone was completed with the help of the collagen, the collagen gradually disappeared. The biological evolution of snail bone and collagen can be well revealed by CARS and SHG, and in addition, the biological evolution of structure and morphology can be clearly observed day by day. Abstract : Using nonlinear optical microscopy of coherent antistokes Raman scattering (CARS), second harmonic generation (SHG) and two‐photo excitation fluorescence, we in situ observed how the collagen and the bone grow synergistically and competitively during nascent biological evolution. The biological evolution of snail bone and collagen can be well revealed by CARS and SHG, and in addition, the biological evolution of structure and morphology can be clearly observed day by day.